Brief in-play cooling breaks reduce thermal strain during football in hot conditions. Issue 8 (August 2019) - Chalmers, Samuel; Siegler, Jason; Lovell, Ric; Lynch, Grant; Gregson, Warren; Marshall, Paul; Jay, Ollie
Abstract: Objectives: The study examined if three feasible strategies involving additional in-play cooling periods attenuate the core (rectal) temperature rise during simulated football matches. Design: Four counterbalanced experimental trials in an environmental chamber set to 35 °C ambient temperature, 55% relative humidity, and 30 °C WBGT. Methods: Twelve healthy well-trained football players completed a regular simulated match (REG), regular simulated match with additional 3-min cooling periods at the 30-min mark of each half inclusive of chilled water consumption (COOLwater ), regular simulated match with additional 3-min cooling periods at the 30-min mark of each half inclusive of chilled water consumption and the application of an ice towel around the neck (COOLtowel ), regular simulated match with an extended (+5 min; total of 20-min) half-time break (HTextended ). Results: The difference in rectal temperature change was significantly lower in the COOLwater (−0.25 °C), COOLtowel (−0.28 °C), and HTextended (−0.21 ° C) trials in comparison to the REG (all p < 0.05). Exercising heart rate and session rating of perceived exertion was lower in the COOLwater (−13 bpm; −1.4 au), COOLtowel (−10 bpm; −1.3 au), and HTextended (−8 bpm; −0.9 au) trials in comparison to the REG trial (all p < 0.05). The cooling interventions did not significantly change skin temperature or thermal sensation in comparison to the REG (all p > 0.05). Conclusions: All three cooling interventions attenuated core body thermal strain during simulated matches. The laboratory-based study supports the use of brief in-play cooling periods as a means to attenuate the rise in core temperature during matches in hot and humid conditions.